My big fat Greek wedding 2 - Hanks, Tom; Wilson, Rita; Goetzman, Gary, 1952-; Jones, Kirk, 1964-; Vardalos, Nia, 1962-; Corbett, John, 1961-; Fatone, Joey, 1977-; Mandylor, Louis; Constantine, Michael; Kazan, Lainie; Martin, Andrea, 1947-; Denault, Jim, 1960-; et al. (Universal City, CA Universal Pictures Home Entertainment, 2016)
In this sequel to the highly successful 2002 motion picture, surprise: a hitherto unmentioned Portokalos family secret is sufficiently likelihood-bending as to force the previous film's characters out of large-screen retirement and back into our hearts for another big and fat Greek wedding.
Originally released as a motion picture in 2016.
Wide screen (2.40:1) presentation
Special features: Gag reel; making the Greekquel; My big fat Greek dinner.
Music, Christopher Lennertz ; editor, Mark Czyzewski ; director of photography, Jim Denault.
Nia Vardalos, John Corbett, Gia Carides, Joey Fatone, Louis Mandylor, Andrea Martin, Michael Constantine, Lainie Kazan, Elena Kampouris, Alex Wolff, Rita Wilson, Jayne Eastwood, Ian Gomez.
MPAA rating: PG-13, for some suggestive material.
Keywords: Greek Americans -- Drama; Married people -- Drama; Families -- Drama; Teenagers -- Drama; Greek Americans -- Drama; DVDs; Comedy; Video recordings for the hearing impaired; Comedy films; Drama; Feature films; Films for the hearing impaired; Fiction films